THE PERFECTIVE ASPECT OF COMPOUND VERBS IN JAPANESE - Jannah, Annisa Nurul; Sumarlam, Sumarlam; Purnanto, Dwi (Universitas Muhammadiyah Semarang, 2019)
This paper will discuss about compound verbs (V + V) that have perfective aspect meaning. The compound verbs are owaru, oeru, and yamu. The compound verbs will be attached to other verbs which are located in front of it. The aim of this paper is to find out the types of verb that are attached to the compound verbs that have the aspect meaning. Thus, it can be seen the types of verb, do the types include activity, retinal, static, or stative verb. From the structure, it can be seen the differences in the use of the three verbs, and whether they can replace each other. Based on the results and data analysis, it can be concluded that owaru and oeru can be attached to activity verb and those can replace each other. Whereas, yamu verb is only attached to static and negative verb which are natural phenomenon and human emotional verb that cannot replace owaru and oeru verb in a sentence because those are not acceptable.